Separator for Separating Solids From a Fluid - Alma Rahat (2020)
A separator for separating solids from a fluid including a tray assembly, the tray assembly including a plurality of nested tray units which define a separator axis and are spaced apart from one another along the separator axis, wherein each tray unit includes comprising an inner surface facing the separator axis 16 extending outwards, away from an aperture in the tray unit disposed at the separator axis, wherein the inner surface comprises an inner portion and an outer portion, wherein the inner portion is disposed between the aperture and the outer portion, and wherein the gradient of the outer portion is greater than the gradient of the inner portion.